How climate change is shaping young people’s health: a participatory, youth co-led study from Bangladesh, Guatemala and Nigeria - Jessie Pinchoff; Karen Austrian; Eno-Obong Etetim; Damilola Babatunde; Eleanor Blomstrom; Sigma Ainul; Toyin Olamide Akomolafe; Brian Medina Carranza; Angel Del Valle (BMJ Global Health)
Introduction Climate change is shaping adolescent and young people’s (AYP) transitions to adulthood with significant and often compounding effects on their physical and mental health. The climate crisis is an intergenerational inequity, with the current generation of young people exposed to more climate events over their lifetime than any previous one. Despite this injustice, research and policy to date lacks AYP’s perspectives and active engagement.Methods Participatory, youth co-led qualitative focus group discussions were held in Bangladesh, Guatemala and Nigeria in mid-2023. A total of 196 AYP ages 12–25 years participated. Open-ended questions elicited responses regarding AYP knowledge, experiences and perceptions of climate change. Using NVivo software, translated transcripts were coded to explore and synthesise key thematic areas.Results Respondents discussed varied climate exposures and associated health risks, for example, how flooding events were impeding access to sexual and reproductive health commodities. Acute climate events like flooding and cyclones increased perceived risk of early marriage and gender-based violence in Bangladesh and Guatemala. In Nigeria, respondents discussed health effects of extreme heat, and how droughts were shifting women into more traditionally male roles in agriculture and income-generating activities, increasing the perceived risk of household tensions and gender-based violence. Commonly reported themes included perceived climate impacts on sexual and reproductive health including early marriage or gender-based violence. Another common theme was anxiety about climate change, its effects on economic and food insecurity in communities and feeling hopeless, lacking agency and not feeling supported by local institutions, all linked with worse mental health.Conclusion Our results summarise how AYP perceive climate change is affecting their physical and mental health, finding similarities and differences across these three settings. Our results can inform the development of policies and programmes that directly address AYP needs in a way that is inclusive and responsive.